Analyzing Cohesion Device of Monologue Texts in Students’ Text Book for Eight Grade in Academic Year 2017/2018 - Muhamad Zayyinul Muttaqin (Universitas Islam Negeri Walisongo Semarang, 2017)
This study aimed to describe the types of cohesive devices that were mostly used and also to find out which one the most cohesive text among texts in Students’ texts book (When English Rings a Bell) for Junior High School at eighth grade in the academic year of 2017/2018. The object of this study was monologue texts that are found in students’ texts book for Junior High School at eight grade in the academic year of 2017/2018. This study used qualitative approach. The researcher analyzed the data; First, the data were analyzed by dividing and numbering sentences into clauses, second, putting the number of cohesive devices into tables based on types, third, putting the number of cohesive devices in the form of a percentage, the last, interpreting based on the result.